Outcome of endoscopic resection of colonic polyps larger than 10 mm in patients with inflammatory bowel disease - Siddhant Yadav; Edward V. Loftus Jr.; W. Scott Harmsen; Louis M. Wong Kee Song; Nayantara Coelho-Prabhu (Endoscopy International Open, 2019)
Background and study aims There are limited published data on endoscopic removal of colorectal polyps by endoscopic mucosal resection (EMR) and endoscopic mucosal dissection (ESD) in patients with inflammatory bowel disease (IBD). Patients and methods We performed a retrospective review of patients with colonic IBD and colonic polyps >10mm who underwent EMR and/or ESD at our institution between January 1, 2012 and June 31, 2016. Results Ninety-seven patients with pathology-confirmed IBD (median disease duration 16 years) were included. Mild or moderate active colitis (in background biopsies) was seen in 85 %. Of the total 124 polyps, location was ascending colon in 44 %, transverse in 15 % and sigmoid in 18.5 %; of the total, 55 % were < 20 mm and 45 % were ≥20mm in maximal diameter. Using the Paris classification, 56 % of polyps were polypoid sessile (Is) polyps, while 38 % were non-polypoid (IIa, IIb, IIc). EMR was used in 118 polyps, three required ESD, and three by combined EMR-ESD. Seventy-two percent were resected en-bloc; 28 % underwent piecemeal resection. Histology included low-grade dysplasia in 75, serrated adenoma in 31, and tubular adenoma in 14 polyps. Chromoendoscopy was used in 33 (26.6 %). Adverse events occurred in three patients. Colectomy was performed in 11 patients within 12 months. Recurrence was seen in 20 polyps, 11 of which were successfully resected en-bloc using EMR. Polyps ≥ 20 mm and polyps treated with APC were found to have a statistically significantly higher risk of recurrence. Conclusion This study demonstrates the efficacy and safety of endoscopic resection of large polyps in patients with IBD, making them effective alternatives to colectomy.